2017
DOI: 10.1002/lary.26859
|View full text |Cite
|
Sign up to set email alerts
|

Work‐related musculoskeletal symptoms among otolaryngologists by subspecialty: A national survey

Abstract: NA. Laryngoscope, 128:632-640, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 10 publications
6
75
0
Order By: Relevance
“…First, this study had a small sample size and was from a single institution, which may limit its generalizability. However, we had an excellent response rate of 68.6%, which compares very favorably to the literature . Additionally, assessment of the REBA score can be subjective, as most postural positions are scored based on both an angular and a time factor.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…First, this study had a small sample size and was from a single institution, which may limit its generalizability. However, we had an excellent response rate of 68.6%, which compares very favorably to the literature . Additionally, assessment of the REBA score can be subjective, as most postural positions are scored based on both an angular and a time factor.…”
Section: Discussionsupporting
confidence: 68%
“…A survey of American pediatric otolaryngologists reported that 62% of practitioners experience pain or discomfort attributed to their surgical practice, but only 31% of the practitioners were aware of ergonomics . Similar rates were reported by a large cohort of otolaryngologists from North America, which also found only a third of practitioners had knowledge of ergonomics …”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations